3=3(b+6)

Simple and best practice solution for 3=3(b+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3=3(b+6) equation:



3=3(b+6)
We move all terms to the left:
3-(3(b+6))=0
We calculate terms in parentheses: -(3(b+6)), so:
3(b+6)
We multiply parentheses
3b+18
Back to the equation:
-(3b+18)
We get rid of parentheses
-3b-18+3=0
We add all the numbers together, and all the variables
-3b-15=0
We move all terms containing b to the left, all other terms to the right
-3b=15
b=15/-3
b=-5

See similar equations:

| 5x÷9=-51 | | (N-6)/3=(n-2)/9 | | .4x+9=25 | | 1/10y-3=-7 | | 14-7c=63 | | 3x-x+4=2x+16 | | 2+-10-3n=24 | | r2+10r+9=0 | | -12=-3x+4x | | 21x+6=17x26 | | 8/3x+1/3x=1/1/3+7/3x | | 2v+2=7(8v+8) | | 9a=17+1 | | 365w=3 | | -(1+7x)-6-(-7-x)=36 | | 1/5x+6=3 | | $15+$0.50=x | | 29x+27=180 | | 2=6a-16 | | N+2=-14-m | | 1/2y+6=-16 | | 3.4z-2.7=0.3z+0.865 | | 8n^2-64=-16n | | 2=6a-1 | | 0.04(3t+6)=0.12(t+3)-0.12 | | 16p2+3p=0 | | -2(r+8)=-31 | | (k+8)/3=-2 | | 3(3.1x-4.2)=6.2x+3.2 | | 48-(3c+4)=4(c+6)+c | | 45z+20=13.4 | | 7x-27+4x=12 |

Equations solver categories